Preparación física y su influencia en el rendimiento físico de los futbolistas del Club Deportivo Eugenio Espejo, cantón Babahoyo, Provincia Los Ríos - Castañeda Chávez, Miguel Ángel (2021)
Soccer is one of the most prominent sports practiced by anyone, whether they are women, men, children, each one with significant qualities to function in this area. Its evolution has marked a space around the world as it has adapted to various cultures to become the favorite sport that is known today. Physical preparation as an influence on the physical performance of soccer players triggers a very important role in the development of skills and qualities that a soccer player must have such as endurance, speed, flexibility, coordination among other factors. The needs of this type of sport entail an estimated time where the footballer requires adequate and systematic physical preparation so that he can develop optimally and pertinently in his sports area. All of these requirements need to be accomplished through preparation guided by professionals who apply fitness methods and resources. That is why the research topic deals with “Physical preparation and its influence on the physical performance of the soccer players of the Eugenio Espejo sports club, Babahoyo canton, Los Ríos Province. From the theme raised, it can be analyzed how physical preparation influences the optimal performance of footballers, giving as a general objective “To determine the influence of physical preparation on the physical performance of the footballers of the Eugenio Espejo sports club, Babahoyo Canton, Los Ríos Province ”, using the appropriate methodology that allows meeting the objectives set.